Inter-organizational sensemaking in the face of strategic meta-problems: Requisite variety and dynamics of participation - Seidl, David; Werle, Felix (Strategic management journal, 2018)
Research summary: When faced with complex strategic problems that exceed their individual sensemaking capacities, organizations often engage in inter-organizational collaboration. This enables them to pool the participants' different perspectives and to grasp the problem at hand more comprehensively. Drawing on data collected from two longitudinal case studies, we examine how those who participate in inter-organizational sensemaking processes are selected and how the particular selection of participants affects the dynamics of the sensemaking process in turn. In our analysis, we show how the selection of specific problem issues influences who joins or withdraws from the collaboration and we identify a mechanism that accounts for changes in the particular dynamics of the sensemaking process over time. Our findings help explain how the process of inter-organizational sensemaking can yield different outcomes. Managerial summary: The ability to make sense of the business environment is central to strategic management. As the complexity of the environment increases and interpreting it becomes more difficult, organizations increasingly turn to inter-organizational collaboration, which allows them to pool their expertise in order to explore strategic issues. We examine how the participants in projects of joint exploration are selected and how the selection of participants affects the process of exploration in turn. More specifically, we describe how the aspects on which collaborating organizations choose to focus influence who joins and who withdraws from a collaboration. We also identify a mechanism that accounts for differences and changes in the dynamics of the sensemaking process over time. These changes affect how the collaborators come to understand their organization's business environment.